Medicare Accountable Care Organizations and Use of Potentially Low-Value Procedures. (April 2019) - Modi, Parth K.; Kaufman, Samuel R.; Borza, Tudor; Oliphant, Bryant W.; Ryan, Andrew M.; Miller, David C.; Shahinian, Vahakn B.; Ellimoottil, Chad; Hollenbeck, Brent K.
Objective. To evaluate the effect of Accountable Care Organizations (ACOs) on the use of vertebroplasty and arthroscopic partial meniscectomy, 2 procedures for which randomized controlled trials suggest similar outcomes to sham surgery and therefore may provide low value. Medicare Shared Savings Program ACOs aim to improve quality and decrease health care spending. Reducing the use of potentially low-value procedures can accomplish both of these goals. Methods. We performed a retrospective cohort study of patients who underwent potentially low-value orthopedic procedures (vertebroplasty and partial meniscectomy) and a control (hip fracture) from 2010 to 2015 using a 20% sample of national Medicare claims. We performed an interrupted time-series analysis using linear spline models to evaluate the count of each procedure per 1000 patients, stratified by ACO participation. Results. We identified 76 256 patients who underwent arthroscopic partial meniscectomy, 44 539 patients who underwent vertebroplasty, and 50 760 patients who underwent hip fracture admission. Arthroscopic partial meniscectomy rates decreased, vertebroplasty rates remained stable, and hip fracture rates increased for both groups during the study period, with similar trends among ACO and non-ACO patients. After January 1, 2013, ACO and non-ACO populations had similar trends for vertebroplasty (ACO incidence rate ratio [IRR] = 1.15 [1.08-1.23] vs non-ACO IRR = 1.11 [1.05-1.16]), meniscectomy (ACO IRR = 1.06 [1.01-1.12] vs non-ACO IRR = 1.03 [0.99-1.07]), and hip fracture (ACO IRR = 1.08 [1.01-1.14] vs non-ACO IRR = 1.08 [1.03-1.13]). Conclusions. ACOs were not associated with a reduction in the frequency of vertebroplasty and arthroscopic partial meniscectomy.